Egg-collar morphology and identity of nine species of Naticidae (Gastropoda) in Taiwan, with an assessment of their phylogenetic relationships. (19th September 2018) - Kang, Dun-Ru; Tan, Koh Siang; Liu, Li-Lian
Abstract: The gross morphology of egg (sand) collars laid by nine naticid species in six genera from Taiwan are described and compared: Paratectonatica tigrina, Notocochlis cernica, N. gualtieriana, N . sp. aff. antoni, Naticarius zonalis, Tectonatica bougei, Sinum haliotoideum (= planulatum ), Mammilla melanostoma and M. melanostomoides . Egg collars and adult animals were collected from Taiwan and its offshore islands, as well as from Four-Way Closure Ridge (1, 648 m depth) in the South China Sea. Mitochondrial COI and 16 S rRNA sequences were obtained from both embryos and adults and the genetic distances of these sequences from maximum-likelihood trees were then compared to determine the identity of the egg collars. Of the egg collars of nine species identified using this procedure, seven are described here for the first time. Each species laid a consistent, distinctive egg collar that differed in the overall shape and size, number of coils, capsule size and packing density in different species. The largest collars, with basal diameters exceeding 8 cm, were laid by M. melanostoma and S. haliotoideum, while the smallest belonged to Notocochlis spp., with basal diameters as small as 1 cm. In the egg collars of all nine species examined, each embryo was enclosed within a single capsule. COI and 16 S sequences from egg collars were analysed together with published sequences from other studies. Seven groups, each with a unique egg-collar morphology, were defined, some of which were coincident with supported phylogenetic clades. These results represent only a small fraction of some 47 species of Naticidae recorded to date from Taiwan, but the use of a combination of morphological and molecular characters appears to be a viable method to identify egg collars. The egg-collar literature involving 52 naticid species worldwide is briefly reviewed in the light of our results.